A Shearlets-based Edge Identification Algorithem for Infrared Image - Rui-bin ZOU; Cai-cheng SHI (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A shearlets-based edge identification algorithem for infrared image is proposed. The algorithem demonstrates the performance of edge detection based on shearlets, combines with the edge hysteresis thresholding, designs steps of edge detection, which is proper to use in infrared images.Simultaneously, with the advantage of edge geometric features provided by the shearlets, infrared image were extracted the direction information of edge of Infrared image, and classified. In computer simulations with this method for infrared image,simulation results conformed to the theory on edge detection based on shearlets. It drew the outline of edge for infrared image, and provided the edge orientation feature. The method is very eventful for target detection, identification, track in infrared image system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3266